Zirconium dioxide carrier catalyst with high copper content, preparation method of zirconium dioxide carrier catalyst and application of zirconium dioxide carrier catalyst in selective hydrogenation preparation of sandalwood 210
Preparation by low-temperature co-precipitation method of high copper content zirconia support catalysts, the problems of insufficient selectivity and environmental pollution in the synthesis of sandalwood 210 are solved, and efficient, stable and environmentally friendly catalytic effects are achieved.
Patent Information
- Application Number
- CN202411348645.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-18
AI Technical Summary
In the synthesis of sandalwood 210, existing catalysts have problems such as insufficient selectivity, fast activity attenuation, complex environmental pollution, or high energy consumption, especially chromium-containing catalysts, which can lead to serious environmental pollution.
The high copper content zirconia support catalyst is prepared by low-temperature co-precipitation combined with simple drying and grinding processes, avoiding high-temperature roasting, simplifying the preparation process, and improving the dispersion and activity of the catalyst through fine grinding.
High activity, high selectivity and good stability are achieved, the conversion rate can reach more than 98%, the selectivity is higher than 95%, and the catalyst has good environmental friendliness and simplicity of industrial production.
Smart Images

Figure BDA0005061692260000011 
Figure BDA0005061692260000061 
Figure BDA0005061692260000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and relates to a catalyst for the selective hydrogenation reaction of unsaturated ketones, and specifically relates to a zirconium dioxide carrier catalyst with a high copper content, a preparation method thereof, and an application of the catalyst in the selective hydrogenation preparation of sandalwood 210. Background Art
[0002] Sandalwood 210, also known as 3-campholenyl-2-butanol, is an important fragrance intermediate with a strong woody aroma. Its molecular structure contains an unsaturated cyclopentene ring and a secondary alcohol functional group. This unique structure gives it an aroma similar to that of natural sandalwood. Therefore, it is widely used in perfumes, cosmetics, soap flavors, and flavor formulas for various household products.
[0003] Traditionally, the synthesis route of sandalwood 210 is mainly achieved through the selective hydrogenation reaction of 3-camphor-enyl-2-butanone. This reaction involves the selective hydrogenation of the ketone group, which requires the catalyst to selectively reduce the carbonyl group to an alcohol while keeping the carbon-carbon double bond in the molecule unchanged, which places high demands on the design of the catalyst. The conversion reaction of 3-camphor-enyl-2-butanone to sandalwood 210 is as follows:
[0004]
[0005] Copper-based catalysts are widely used in organic synthesis due to their high efficiency, stability and relatively low cost. Compared with other precious metal catalysts, such as palladium or platinum, copper-based catalysts have obvious advantages in terms of environmental friendliness and economy. However, in the synthesis of sandalwood 210, the existing technology still has many problems:
[0006] 1. Traditional copper-chromium (Cu-Cr) catalyst: As described in CN101125798A and CN1404922A, although it has high activity, usually can reach 90-93% conversion rate and 88-92% selectivity, the selectivity is insufficient, and it cannot be recycled, and there is a problem of heavy metal pollution.
[0007] 2. Precious metal modified Cu-Cr catalyst: As described in CN1398670A and CN1562477A, although it has good activity and can achieve a conversion rate of more than 95%, its selectivity is usually less than 94%, and it is expensive, cannot be recycled, has too high a cost, and still contains toxic chromium elements.
[0008] 3. Other types of catalysts: such as the CuO / Cr2O3 and Cu / SiO2 mixed catalysts disclosed in DE3425758, and the copper-aluminum catalyst described in CN111298797B, although they have been improved in some aspects, they still have problems such as complex preparation, high energy consumption, and insufficient selectivity.
[0009] 4. Copper-zirconium-silicon dioxide catalyst: As described in CN107930627B, although the preparation process is simplified, it still requires high-temperature multi-step calcination and other steps.
[0010] These existing technologies generally have the following problems: environmental pollution, insufficient selectivity, rapid activity decay, harsh reaction conditions, complex preparation process or high energy consumption, etc. In particular, chromium-containing catalysts, because chromium is a highly toxic carcinogen, will cause serious environmental pollution problems in production and waste catalyst recovery and treatment.
[0011] Therefore, the development of a new catalyst that is efficient, stable, environmentally friendly and easy to prepare is of great significance for the green synthesis of sandalwood 210. Summary of the invention
[0012] In view of the shortcomings of the prior art, the present invention aims to provide a high copper content zirconium dioxide supported catalyst for efficient synthesis of sandalwood 210, which has the characteristics of high activity, high selectivity, good stability and environmental friendliness. The present invention also provides a simple, controllable and environmentally friendly catalyst preparation method.
[0013] The present invention is achieved through the following technical solutions:
[0014] A high copper content zirconium dioxide carrier catalyst, calculated by molar percentage of metal elements, comprises 45%-60% copper, 37%-54% zirconium and 1%-3% magnesium.
[0015] A further improvement of the present invention is:
[0016] A method for preparing a high copper content zirconium dioxide supported catalyst, using a low temperature coprecipitation method combined with a simple drying and grinding process, specifically comprising the following steps:
[0017] (1) dissolving copper salt, zirconium source and a small amount of magnesium source in water to prepare a mixed solution;
[0018] (2) reacting the mixed solution with an alkali solution to perform a coprecipitation process to obtain a slurry; during the coprecipitation process, a mixture of hydroxides and / or basic salts of copper, zirconium, and magnesium is mainly generated.
[0019] (3) subjecting the slurry to solid-liquid separation, and drying the obtained solid component at low temperature to obtain a precursor;
[0020] (4) Grinding the precursor to obtain the final catalyst.
[0021] The catalyst preparation process of the present invention does not require high-temperature calcination, and a high-activity catalyst can be obtained only through low-temperature drying and fine grinding.
[0022] Furthermore, the copper salt is one or a mixture of two or more of copper nitrate, copper sulfate or copper chloride;
[0023] and / or, the zirconium source is zirconium oxychloride (ZrOCl2·8H2O) or zirconium nitrate (Zr(NO3)4·5H2O) or a mixture of the two;
[0024] And / or, the magnesium source is magnesium nitrate or magnesium chloride or a mixture of the two.
[0025] Furthermore, in terms of molar percentage of metal elements, the copper salt is 45%-60%, the zirconium source is 37%-54%, and the magnesium source is 1%-3%.
[0026] Furthermore, the alkali solution is one or a mixture of two or more of ammonia water, sodium hydroxide solution or sodium carbonate solution.
[0027] Furthermore, the low-temperature drying temperature is 60°C-110°C, and the time is 6h-24h;
[0028] Furthermore, the grinding process needs to control the particle size distribution so that particles larger than 300 meshes account for 80% or more, which helps to improve the dispersibility and activity of the catalyst.
[0029] During the drying and grinding process, due to the influence of temperature (above 60°C), some hydroxides (such as copper hydroxide) in the precipitate may gradually dehydrate and partially convert into the corresponding metal oxides. This mild conversion process helps to form highly dispersed active components while maintaining high catalyst activity.
[0030] A further improvement of the present invention is:
[0031] Application of a high copper content zirconium dioxide supported catalyst in catalytic hydrogenation synthesis of sandalwood 210.
[0032] Furthermore, the specific application includes the following steps: reacting a high copper content zirconium dioxide carrier catalyst, a raw material 3-borneolene-2-butanone and a solid base at 140° C.-180° C. for 2-4 hours under a hydrogen atmosphere.
[0033] Furthermore, the solid base is one or a mixture of two or more of cesium hydroxide, potassium hydroxide, sodium hydroxide or lithium hydroxide.
[0034] Furthermore, the amount of the solid base is 0.05-0.5% of the mass of 3-camphoryl-2-butanone;
[0035] And / or, the amount of the high copper content zirconium dioxide carrier catalyst is 3-10% of the mass of 3-camphoryl-2-butanone.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The present invention achieves high dispersion and strong interaction of active components by precisely controlling the copper loading, introducing a small amount of alkaline auxiliary agent (such as magnesium oxide), adopting low-temperature coprecipitation method and innovative grinding process, and obtains a catalyst system in which highly dispersed copper species are loaded on a zirconium dioxide carrier. In the preparation process of the catalyst, low-temperature coprecipitation method and mild heat treatment are adopted, and high-temperature roasting is not required. The operation is simple, the preparation process is energy-saving, the preparation process is greatly simplified, and it is easy to industrialize production. The raw materials used to prepare the catalyst are cheap, and the use of toxic heavy metals is completely avoided. The preparation process and the use process have little impact on the environment, which conforms to the concept of green chemistry.
[0038] The catalyst of the present invention exhibits excellent performance in the synthesis of sandalwood 210, has high activity and high selectivity, the conversion rate can reach more than 98%, and the selectivity is higher than 95%. It has good stability, and the catalytic activity and selectivity remain stable during continuous use, and has a long service life. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with specific embodiments.
[0040] Example 1: Preparation of high copper content zirconium dioxide supported catalyst A
[0041] a) Dissolve 11.6 g of copper nitrate (Cu(NO3)2·3H2O), 11.2 g of zirconium oxychloride (ZrOCl2·8H2O), and 0.5 g of magnesium nitrate (Mg(NO3)2·6H2O) in 200 ml of deionized water, and stir until completely dissolved.
[0042] b) Slowly add 28 wt% ammonia water under stirring (500 rpm). The initial solution pH is about 3.5, and the pH gradually increases with the addition of ammonia water. When the pH reaches 7, slow down the dripping speed and accurately control the final pH between 9-10. A total of about 20-25 ml of ammonia water is used.
[0043] c) Continue stirring the reaction at room temperature (25±2°C) for 2 hours.
[0044] d) Filter and wash three times with equal volumes of deionized water.
[0045] e) drying at 65° C. for 18 hours to obtain a precursor.
[0046] f) The dried precursor was ground and measured using a laser particle size analyzer, and the proportion of particles larger than 300 meshes reached 83.5%, thereby obtaining a blue catalyst A.
[0047] Example 2: Preparation of high copper content zirconium dioxide supported catalyst B
[0048] a) 13.3 g of copper sulfate (CuSO4·5H2O), 10.5 g of zirconium nitrate [Zr(NO3)4·5H2O], and 0.4 g of magnesium chloride (MgCl2·6H2O)
[0049] Dissolve in 200 ml of deionized water and stir well.
[0050] b) Slowly drop 4 wt% sodium hydroxide solution under stirring (800 rpm). The initial solution pH is about 3.0, and the pH gradually increases with the addition of NaOH solution. When the pH reaches 6.5, slow down the dripping speed and accurately control the final pH between 9-10. A total of about 140-150 ml of NaOH solution is used.
[0051] c) Continue stirring the reaction at room temperature for 3 hours.
[0052] d) Filter and wash three times with equal volumes of deionized water.
[0053] e) drying at 65° C. for 20 hours to obtain a precursor.
[0054] f) The dried precursor was ground and measured using a laser particle size analyzer. The particles with a size of 300 mesh or larger accounted for 85.2%, thereby obtaining a blue catalyst B.
[0055] Example 3: Preparation of high copper content zirconium dioxide supported catalyst C
[0056] a) Dissolve 14.5 g of copper acetate [Cu(CH3COO)2·H2O], 12.0 g of zirconium oxychloride (ZrOCl2·8H2O), and 0.6 g of magnesium acetate [Mg(CH3COO)2·4H2O] in 250 ml of deionized water and stir for 30 minutes to form a uniform solution.
[0057] b) Slowly drop 10 wt% ammonia at 10°C. The initial solution pH is about 4.0, and the pH gradually increases with the addition of ammonia. When the pH reaches 8, slow down the dripping speed and accurately control the final pH between 9.5-10. A total of about 80-90 ml of ammonia is used.
[0058] c) Continue stirring the reaction at 10°C for 4 hours.
[0059] d) Filter and wash with deionized water three times.
[0060] e) drying at 80° C. for 15 hours to obtain a precursor.
[0061] f) The dried precursor was ground and measured using a laser particle size analyzer. The particles with a size of 300 mesh or larger accounted for 82.8%, thereby obtaining a blue catalyst C.
[0062] Example 4: Preparation of high copper content zirconium dioxide supported catalyst D
[0063] a) Dissolve 12.8 g of copper nitrate [Cu(NO3)2·3H2O], 13.0 g of zirconium nitrate [Zr(NO3)4·5H2O], and 0.4 g of magnesium nitrate [Mg(NO3)2·6H2O] in 300 ml of ethanol / water mixed solvent (volume ratio 1:1) and stir well.
[0064] b) Slowly add 10 wt% sodium carbonate solution at 10°C. The initial solution pH is about 3.2. As the Na2CO3 solution is added, the pH gradually increases. When the pH reaches 7.5, slow down the dripping speed and accurately control the final pH between 8.5-9.5. A total of about 70-75 ml of Na2CO3 solution is used.
[0065] c) Continue stirring the reaction at 10°C for 3 hours.
[0066] d) Filter by suction, and wash with ethanol / water mixed solvent (1:1) for 4 times.
[0067] e) drying at 75° C. for 16 hours to obtain a precursor.
[0068] f) The dried precursor was ground and measured using a laser particle size analyzer, and the proportion of particles larger than 300 meshes reached 87.5%, thereby obtaining a blue catalyst D.
[0069] Example 5: Preparation of Sandalwood 210 (using catalyst A)
[0070] a) 200 g (0.97 mol) of 3-camphoryl-2-butanone, 10 g of catalyst A and 0.1 g of KOH were added to a 250 ml autoclave.
[0071] b) Seal the reactor and replace it with hydrogen three times.
[0072] c) Fill with hydrogen to 30 bar, raise the temperature to 170°C, and stir to react for 3 hours.
[0073] d) Cool and take samples for analysis by GC-MS.
[0074] After sampling and analysis, the conversion rate of 3-borneol-2-butanone in this example was 99.2%, and the selectivity of sandalwood 210 was 96.8%.
[0075] Example 6: Preparation of Sandalwood 210
[0076] In this example, the catalyst B prepared in Example 2 was used, and other operations were substantially the same as those in Example 5. Sampling and analysis showed that the conversion rate of 3-camphoryl-2-butanone in this example was 98.7%, and the selectivity of sandalwood 210 was 95.9%.
[0077] Example 7: Preparation of Sandalwood 210
[0078] In this example, the catalyst C prepared in Example 3 was used, and other operations were substantially the same as those in Example 5. Sampling and analysis showed that the conversion rate of 3-camphoryl-2-butanone in this example was 98.5%, and the selectivity of sandalwood 210 was 96.2%.
[0079] Example 8: Preparation of Sandalwood 210
[0080] In this example, the catalyst D prepared in Example 4 was used, and other operations were substantially the same as those in Example 5. Sampling and analysis showed that the conversion rate of 3-borneolyl-2-butanone in this example was 98.0%, and the selectivity of sandalwood 210 was 96.5%.
[0081] Example 9: Stability test of catalyst A
[0082] Catalyst A was used to carry out the reaction five times continuously, and the catalyst was recovered after each reaction and directly used for the next reaction without regeneration. The operation was the same as in Example 5, and the test results are shown in the following table:
[0083] Number of applications Conversion rate of 3-borneolyl-2-butanone Sandalwood 210 Selective 1 98.6% 96.8% 2 98.9% 96.5% 3 98.5% 96.1% 4 98.4% 95.9% 5 98.0% 95.5%
[0084] It can be seen from the above table that catalyst A exhibits excellent stability and reusability.
[0085] Example 10: Optimization of reaction conditions (taking catalyst A as an example)
[0086] 1. Temperature effect: The reaction was carried out at 160°C, 165°C, 170°C, 175°C and 180°C, and the other conditions were the same as those in Example 5. The reaction results are shown in the following table:
[0087] Reaction temperature Conversion rate of 3-borneolyl-2-butanone Sandalwood 210 Selective 160℃ 96.80% 95.20% 165℃ 97.90% 96.10% 170℃ 98.60% 96.80% 175℃ 98.40% 96.50% 180℃ 98.00% 96.00%
[0088] The results show that the best performance is achieved at 170°C, with both conversion and selectivity reaching the highest levels.
[0089] 2. Effect of pressure: The reaction was carried out under hydrogen pressures of 25 bar, 28 bar, 30 bar, 32 bar and 35 bar. Other conditions were the same as those in Example 5.
[0090]
[0091]
[0092] The results show that the reaction effect is best at 30 bar, and further increasing the pressure has no obvious effect on performance improvement.
[0093] 3. Optimization of catalyst dosage: 3%, 5%, 7% and 10% of the mass of the catalyst A were used for the reaction, and the other conditions were the same as those in Example 5.
[0094] Catalyst A dosage Conversion rate of 3-borneolyl-2-butanone Sandalwood 210 Selective 3% 97.20% 95.90% 5% 98.60% 96.80% 7% 98.80% 96.90% 10% 98.90% 96.90%
[0095] The results show that a good balance can be achieved when the catalyst dosage is 5%, and further increasing the dosage does not significantly improve the effect.
[0096] Comparative Example 1: Commercial Cu / Cr2O3 Catalyst
[0097] The reaction was carried out using a commercially available Cu / Cr2O3 catalyst (copper content 40 wt%) under the same conditions as in Example 5. Sampling analysis showed that the conversion rate of 3-borneol-2-butanone in this comparative example was 94.6%, and the selectivity of sandalwood 210 was 90.3%.
[0098] Comparative Example 2: Cu / ZrO2 Catalyst without MgO
[0099] The Cu / ZrO2 catalyst was prepared according to the method of Example 1, but without adding a magnesium source. The reaction was carried out under the same conditions as in Example 5. After sampling and analysis, the conversion rate of 3-borneol-2-butanone in this comparative example was 97.8%, and the selectivity of sandalwood 210 was 91.5%.
[0100] From the comparative experimental results, it can be seen that the high copper content zirconium dioxide supported catalyst of the present invention is superior to the traditional Cu / Cr2O3 catalyst and the Cu / ZrO2 catalyst without MgO in terms of activity and selectivity. At the same time, the catalyst of the present invention avoids the use of toxic chromium elements and is more environmentally friendly.
[0101] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A high copper content zirconium dioxide supported catalyst, characterized in that: Calculated by molar percentage of metal elements, copper is 45%-60%, zirconium is 37%-54%, and magnesium is 1%-3%.
2. The method for preparing a high copper content zirconium dioxide supported catalyst according to claim 1, characterized in that: The following steps are involved: (1) dissolving copper salt, zirconium source and a small amount of magnesium source in water to prepare a mixed solution; (2) reacting the mixed solution with an alkali solution to obtain a slurry; (3) subjecting the slurry to solid-liquid separation, and drying the obtained solid component at low temperature to obtain a precursor; (4) Grinding the precursor to obtain the final catalyst.
3. The method for preparing a high copper content zirconium dioxide supported catalyst according to claim 2, characterized in that: The copper salt is one or a mixture of two or more of copper nitrate, copper sulfate or copper chloride; And / or, the zirconium source is zirconium oxychloride or zirconium nitrate or a mixture of the two; And / or, the magnesium source is magnesium nitrate or magnesium chloride or a mixture of the two.
4. The method for preparing a high copper content zirconium dioxide supported catalyst according to claim 2 or 3, characterized in that: Calculated by mole percentage of metal elements, the copper salt is 45%-60%, the zirconium source is 37%-54%, and the magnesium source is 1%-3%.
5. The method for preparing a high copper content zirconium dioxide supported catalyst according to claim 2, characterized in that: The alkali solution is one or a mixture of two or more of ammonia water, sodium hydroxide solution or sodium carbonate solution.
6. The method for preparing a high copper content zirconium dioxide supported catalyst according to claim 2, characterized in that: The low-temperature drying temperature is 60° C.-110° C., and the time is 6 hours-24 hours. When the dried precursor is ground, the particles with a particle size of 300 mesh or more account for 80% or more.
7. Use of a high copper content zirconium dioxide supported catalyst as claimed in claim 1 in catalytic hydrogenation synthesis of sandalwood 210.
8. The use of a high copper content zirconium dioxide supported catalyst according to claim 7 in catalytic hydrogenation synthesis of sandalwood 210, characterized in that: The method comprises the following steps: reacting a high copper content zirconium dioxide carrier catalyst, a raw material 3-borneolyl-2-butanone and a solid base at 140-180° C. for 2-4 hours under a hydrogen atmosphere.
9. The use of a high copper content zirconium dioxide supported catalyst according to claim 8 in catalytic hydrogenation synthesis of sandalwood 210, characterized in that: The solid alkali is one or a mixture of two or more of cesium hydroxide, potassium hydroxide, sodium hydroxide or lithium hydroxide.
10. Use of a high copper content zirconium dioxide supported catalyst according to claim 8 or 9 in catalytic hydrogenation synthesis of sandalwood 210, characterized in that: The amount of the solid base is 0.05-0.5% of the mass of 3-camphoryl-2-butanone; And / or, the amount of the high copper content zirconium dioxide carrier catalyst is 3-10% of the mass of 3-camphoryl-2-butanone.
Citation Information
Patent Citations
Method for preparing 3- bornylene
CN101125798A
A furfural hydrogenation catalyst, its preparation method and application, and a method for producing furfuryl alcohol by liquid-phase hydrogenation of furfural.
CN107930627B
Copper-aluminum catalysts and their preparation methods, and a method for preparing 3-borneolenyl-2-butanol.
CN111298797B
Catalyst for liquid phase hydrogenation of furaldehyde to prepare furfuralcohol and its use
CN1398670A
Catalyst for preparing furancarbinol from liquid-phase furol hydrogenation and use thereof
CN1404922A